COMPREHENSIVE ENVIRONMENTAL ASSESSMENT OF THE STATE OF GREEN SPACES OF THE URBAN ENVIRONMENT OF THE CITY OF ATYRAU (Eurasian Journal of Ecology, 2025)
The article presents a comprehensive ecological assessment of the urban green spaces in Atyrau, one of the major industrial centers of Kazakhstan. The study applied modern environmental monitoring methods, including tree and shrub inventory, evaluation of biological conditions, calculation of per capita green space availability, and determination of dust load levels. The survey revealed a total of 15587 trees and shrubs, of which 82% were classified as «healthy». The average integral biological assessment score was 4.8, corresponding to the category of a «healthy stand», while the vitality index calculated by Alekseev’s methodology reached 92.3%, indicating stable functioning of urban greenery. However, the provision of green spaces per capita was only 0.59 m², which is significantly below the World Health Organization standard (9 m²/person) and Kazakhstan’s national standards (6–12 m²/person). Furthermore, the average dust load index was recorded at 3080 mg/m²/day, exceeding the permissible limit by more than three times. These findings highlight a contradiction between the relatively high biological quality of green plantations and their extremely insufficient spatial availability. The authors emphasize the urgent need for large-scale expansion of green areas, introduction of plant species adapted to arid climates and industrial stress, implementation of innovative air purification technologies, and systematic integration of green infrastructure into urban planning. This study holds both scientific and practical significance as it establishes a foundation for strategies of sustainable urban development under conditions of intensive industrial impact.Keywords: green spaces, urban environment, dust load, biological stability, Atyrau city, ecological state